107 A Novel Transition Clinic For Adolescents and Young Adults With Non-Malignant Blood Disorders. (19th August 2020) - Jegathesan, Thivia; Roth, Megan; Florence, Melissa; Mistry, Niraj; Bonifacio, Herbert J; Sgro, Michael; Baker, Jillian
Abstract: Background: Transition clinics have been introduced as a way to address the unique needs of adolescent and young adult populations (AYA). AYA transition clinics for non-malignant blood disorders that require continuous care and management such as chronic immune thrombocytopenia (ITP) and Hereditary Spherocytosis (HS), have not been evaluated to date. In addition, the concerns and barriers to accessing care among this population have not been previously described. Objectives: To explore the needs of AYA patients with a non-malignant hematological condition in order to improve their transition to the adult healthcare system through a transition clinic. Design/Methods: A prospective cross-sectional survey study was conducted with AYA patients with a new or existing non-malignant hematological condition attending an AYA clinic in Toronto. Patients were prospectively provided a survey prior to their clinic appointment via text message. Results: Twenty eight patients completed the survey. Most of the patients were female (84.6%) and between 16-25 years of age. Patients were in school (57%) or working (25%). Over half of the patients (53%) reported to seeing a doctor at least once a year. In order to attend clinic appointments, 61% reported taking public transportation, 10% of patients receive a ride from their family and 29% of patients either drove themselves or walked/biked to clinic. Twenty-seven percent of patients were unsure of their condition, 50% did not know the cause of their condition, and over 70% of patients were concerned about their health at least once a day. Almost all patients had concerns about transitioning to adult care with concerns including 1) Adult care not understanding their needs, 2) Increased responsibility of their care and 3) Working with a new clinical care team. Despite their concerns of transition to an adult healthcare system, 67% of patients reported taking on most of the responsibility of their health including booking appointments, and taking their medication. However, the proportion of patients who wanted their parents at their appointments equaled those that did not. Finally, patients reported the following areas of their life their health has negatively impacted; 1) School, 2) Social interactions with family and friends, and 3) Work. Conclusion: As seen in other diseases, AYA patients with non-malignant hematological conditions have concerns about transitioning to adult care. Young adults have varying degrees of interest and abilities regarding self-care, and are particularly vulnerable to the impact of health issues. Several factors need to be considered when caring for this unique population, that if addressed can improve the transition experience.